Laminar Free Convection In Horizontal Annulus Filled With Glass Beads And With Annular Fins On The Inner Cylinder (Journal of Engineering, 2013)
An experimental and numerical study has been carried out to investigate the heat transfer by natural convection and radiation in a two dimensional annulus enclosure filled with porous media (glass beads) between two horizontal concentric cylinders. The outer cylinders are of (100, 82 and70mm) outside diameters and the inner cylinder of 27 mm outside diameter with (or without) annular fins attached to it. Under steady state condition; the inner cylinder surface is maintained at a high temperature by applying a uniform heat flux and the outer cylinder surface at a low temperature inside a freezer. The experiments were carried out for an annulus filled with glass beads at a range of modified Rayleigh number (4.9 ≤ Ra≤ 69), radiation parameter (0